Plataformas digitales tras decisión de la Gimnasta Olímpica Simone Biles - Conforme Mosquera, Mercedes Juliana (2021)
This study analyzed the information treatment in the digital platforms Instagram and Facebook of the newspapers El Universo and Extra, after the decision of the Olympic gymnast Simone Biles, to leave the Tokyo 2020 Olympics, due to mental health problems. The aforementioned social networks were considered, because they are a source of massive information that manages to influence the way people think and act, also because the issue of mental health has been considered for years as a taboo. To collect the information, it was necessary to apply the quantitative and qualitative methodology, by means of exploratory, descriptive, diagnostic and documented research, by means of the technique of data collection observation, the subject of study was the news of the media mentioned above, about the decision of Biles in July 27 and 28 of this year, obtaining 2 informative pieces between both newspapers. Where, the results found showed that there are few pieces about this fact, identifying that the media gives little space to this problem, allowing it to go unnoticed, because of this is recommended a few steps for the appropriate journalistic treatment on this topic.